The Safety of Blood Flow Restriction Combined with Stepping Aerobic Exercise in Older Adults with Sarcopenia - Zhang H; Liu S; Mao Z; Niu K; Li X; Yin T; Wang F; Wang L (Clinical Interventions in Aging)
Hui Zhang,1,2,* Shulian Liu,3,* Zhiyu Mao,2 Kewen Niu,2 Xinwei Li,2 Tongtong Yin,2 Fangfang Wang,2 Li Wang2 1School of Nursing, Suzhou Vocational Health College, Jiangsu, 215009, People’s Republic of China; 2School of Nursing, Suzhou Medical College of Soochow University, Suzhou, Jiangsu, 215006, People’s Republic of China; 3Luoyang Polytechnic, Henan, 471000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Li Wang, School of Nursing, Suzhou Medical College of Soochow University, No. 1 Shizi Street, Suzhou, Jiangsu, 215006, People’s Republic of China, Tel +86-512-6522-1499, Fax +86-512-6512-5097, Email li-wang-1@suda.edu.cnPurpose: This study aimed to explore the safety of blood flow restriction combined stepping aerobic exercise (BFR-SAE) using elastic and non-elastic cuffs at varying pressures in older adults with sarcopenia.Methods: Older adults with sarcopenia were selected by convenience sampling method and underwent BFR-SAE using elastic and non-elastic cuffs at 20%, 40%, and 60% limb occlusion pressure (LOP). Exercise response and adverse events were recorded.Results: Thirty-one participants (84.81 ± 6.19 years old) completed the tests. During the non-elastic cuffs test, 31 participants completed at 20% LOP, and 4 (12.9%) dropped from 40% to 20% LOP. At 60% LOP, 19 (61.3%) and 3 (9.7%) dropped to 40% and 20% LOP, respectively. In the elastic cuffs tests all participants completed at 20% and 40% LOP. At 60% LOP, 9 (29.0%) dropped to the interface pressure corresponding to 40% LOP. General exercise responses were lower with elastic cuffs at 40% LOP (22.6% vs 45.2%) and 60% LOP (41.9% vs 51.6%), with higher completion rate than non-elastic cuffs (40% LOP: 100% vs 87.1%; 60% LOP: 71.0% vs 29.0%). Among the results of systolic and diastolic blood pressure (SBP and DBP), pulse rate (P) and pulse oxygen saturation (SpO2), differences were found in BP and P at different time points (P< 0.05) within each pressure, but no significant difference between different pressures. Non-elastic cuffs caused significant increases in SBP, DBP, and P from rest, while only SBP and P showed significant increases in elastic cuffs group. Pain scores were 0 for both cuffs after tests, the adverse events rate was 1.1% and rating of perceived exertion all reached moderate-intensity of exercise.Conclusion: Elastic cuffs for BFR-SAE induced milder exercise responses and higher completion rates, suggesting better safety and feasibility than non-elastic cuffs in older adults with possible sarcopenia.Keywords: blood flow restriction, aerobic exercise, sarcopenia, safety, older adults